La confiance et le soupçon - Anne-Marie Gagné (Communication)
This article investigates the dynamics of the relationship of trust between the public relations officer and the organization’s stakeholders, specifically within the current context of civil society’s concerns regarding corporate social responsibility (CSR). Our current doctoral research examines several models of trust from fields related to public relations, with the goal of developing a trust relationship model that is specific to public relations.